Hard alloy material

By adding chromium powder and other elements to WC-Fe cemented carbide, the balanced area is expanded, and the pore and radioactive problems in the manufacturing of WC-Fe cemented carbide are solved, and dense cemented carbide with high hardness and fracture toughness is achieved. Neutron shielding in fusion nuclear reactors.

CN119137296APending Publication Date: 2024-12-13ELEMENT SIX LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380028609.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-03-30
Filing Date
2023-03-14
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The prior art is difficult to manufacture WC-Fe cemented carbide blocks that are free of pores and have high hardness and fracture toughness in fusion nuclear reactors, especially due to the narrowness of the two-phase region equilibrium coexistence and radioisotope lifetime of iron-based binders. .

Method used

By adding chromium powder to WC-Fe grade powder, the chemical composition is adjusted to expand the equilibrium area of ​​the W-C-Fe phase diagram, ensuring the equilibrium state of WC and Fe-based binder in cemented carbide, and sintering at high temperature using vacuum sintering process , the chromium content is controlled between 1 wt.% and 6 wt.%, and elements such as Si, Ti, V, Ge, Ta, Pb and Mn are further added to optimize the microstructure.

Benefits of technology

It has achieved the production of dense cemented carbides without η phase or free carbon within the production scale, with high Vickers hardness and Papillar fracture toughness, suitable for neutron shielding, low porosity, and suitable for fusion nuclear reactor wall materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119137296A_ABST
    Figure CN119137296A_ABST
Patent Text Reader

Abstract

A cemented carbide body for neutron shielding and a method of making the same, the cemented carbide body containing WC, Fe, and Cr wherein the Cr is present in an amount of about 1 wt.% to about 150 wt.% relative to the Fe content, the cemented carbide body comprising WC grains, cementite grains, and Cr, W, and C dissolved in an Fe-based binder matrix material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure generally relates to cemented carbide materials and blocks including the same. Background Art

[0002] Fusion nuclear reactors for fusion power plants currently under intensive development require protective materials to be protected from the intense neutron radiation caused by the nuclear fusion process in extremely high temperature plasma. The resulting high-energy neutrons emitted from the plasma must be slowed down (moderated) and captured (absorbed) by the wall of the containment vessel around the plasma. The most suitable material for this is known to be tungsten carbide (WC). However, it is impossible to produce a 100% dense block for the reactor wall from pure tungsten carbide without any metal binder. In addition, any pores must be avoided in the wall material.

[0003] Conventionally, cobalt (Co)-based binders are used in the manufacture of cemented carbides, however, conventional WC-Co cemented carbides required for neutron shielding are problematic because cobalt remains radioactive for a long time, according to MR Gilbert, T. Eade et al. (Waste implications from minor impurities in European DEMO materials. Nuclear Fusion, April 2019, DOI: 10.1088 / 1741-4326 / ab154e). According to the same reference, iron is a significantly better binder material in terms of the lifetime of its radioactive isotopes, making WC-Fe cemented carbides preferred for the manufacture of blocks that form reactor walls required for neutron shielding. However, it is well known (see, for example, B. Uhrenius, H. Pastor, E. Pauty, On the composition of Fe-Ni-Co-WC-based cemented carbides, Int. J Refractory Met Hard Mater, 15 (1997) 139-149) that the two-phase region of cemented carbides with iron-based binders at 1000° C., i.e., the region in which only the carbide phase and the binder phase coexist in equilibrium, is very narrow (about 0.01 wt.% or less), more than 10 times lower than that of conventional WC-Co cemented carbides. This creates significant difficulties in the production of cemented carbides with iron binders, because even very slight deviations in the carbon content of the initial WC-Fe graded powder and in the atmosphere of the sintering furnace lead to the formation of extremely brittle η phase or free carbon. Based on this, WC-Fe cemented carbide cannot be manufactured in the cemented carbide industry because it is almost impossible to produce it without inclusions of eta phase or free carbon, which makes it very brittle and unacceptable for manufacturing and brazing the above-mentioned blocks for fusion nuclear reactor walls.

[0004] The main object of the present invention is to overcome the above difficulties. Summary of the invention

[0005] The object of the present invention is achieved by alloying the binder phase with a chemical element that remains radioactive for a relatively short period of time. It has been surprisingly found that the addition of powders with different chemical elements, in particular chromium, to WC-Fe grade powders in the specific amounts described herein widens the region of the WC-Fe phase diagram in which only carbide phases (i.e. WC and cementite) and metallic binder (i.e. Fe-based binder) exist in equilibrium, thus ensuring the possibility of manufacturing such cemented carbides on a production scale without major technical difficulties.

[0006] Accordingly, in a first aspect of the present invention, there is provided a cemented carbide body for neutron shielding, the cemented carbide body containing, for example comprising, consisting of or consisting essentially of WC, Fe and Cr, wherein the Cr is present in an amount equal to or less than 6 wt.% relative to the Fe content, the microstructure of the cemented carbide body comprising, consisting of or consisting essentially of WC grains, cementite grains, and Cr, W and C dissolved in an Fe-based binder matrix material.

[0007] As an option, the cemented carbide body contains up to 5 wt. % Si, Ti, V, Ge, Ta, Pb and / or Y and combinations thereof, relative to the iron content.

[0008] As an option, the cemented carbide body comprises up to 50 wt. % Mn relative to the Fe content.

[0009] According to a second aspect of the present invention, there is provided a cemented carbide body for neutron shielding, the cemented carbide body containing, e.g., comprising, consisting of, or consisting essentially of WC, Fe and Cr, wherein the Cr is present in an amount of about 1 wt.% to about 150 wt.% relative to the Fe content, the cemented carbide body comprising, consisting of, or consisting essentially of WC grains, cementite grains, and Cr, W and C dissolved in an Fe-based binder matrix material.

[0010] As an option, Cr is present in an amount of about 1 wt. % to about 90 wt. % relative to the Fe content.

[0011] As an option, Cr is present in an amount of about 1 wt. % to about 10 wt. % relative to the Fe content.

[0012] As an option, Cr is present in an amount of about 1 wt. % to about 6 wt. % relative to the Fe content.

[0013] As an option, Cr is present in an amount of about 5 wt. % to about 90 wt. % relative to the Fe content.

[0014] As an option, Cr is present in an amount of about 5 wt. % to about 10 wt. % relative to the Fe content.

[0015] As an option, the cemented carbide body has a Vickers hardness of at least 15 GPa. The Vickers hardness is measured according to ISO 6507-1:2018 (Metallic materials-Vickers hardness test-Part 1: Test method).

[0016] Alternatively, the cemented carbide body has a strength of at least 7 MPa m 1 / 2 The Palmquist fracture toughness is measured according to ISO 28079:2009 (Hardmetals-Palmqvist toughness test).

[0017] As an option, the cemented carbide body comprises less than 0.01 wt.% free carbon. Free carbon herein means carbon present in the cemented carbide body in elemental form, for example in the form of graphite.

[0018] As an option, the cemented carbide body is substantially free of free carbon.

[0019] As an option, the cemented carbide body comprises less than 0.01 wt. % eta phase.

[0020] As an option, the cemented carbide body is substantially free of eta phase.

[0021] As an option, the cemented carbide body has a porosity of less than 1%.

[0022] As an option, the cemented carbide body has a porosity of less than 0.1%.

[0023] As an option, the carbide body is fully dense.

[0024] As an option, the cemented carbide body contains no porosity.

[0025] The characterization of porosity, carbon defects and eta-phase content is carried out according to ISO 4499-4:2016 (Hardmetals-Metallographic determination of microstructure-Part 4: Characterization ofporosity, carbon defects and eta-phase content).

[0026] As an option, the cemented carbide body further comprises up to 5 wt. % Si, Ti, V, Ge, Ta, Pb and / or Y and combinations thereof, relative to the iron content.

[0027] As an option, the cemented carbide body further comprises up to 50 wt. % Mn relative to the Fe content.

[0028] According to a third aspect of the present invention, there is provided a method for preparing a cemented carbide body as described herein, the method comprising: grinding powders of tungsten carbide, iron and chromium-containing material together; pressing the ground powder to form a green body; sintering the green body in a vacuum at a temperature not exceeding 1300°C and for a period of at least 15 minutes; and cooling the sintered body.

[0029] As an option, the method further comprises adding Si, Ti, V, Ge, Ta, Pb, Y and / or Mn in the form of carbides, nitrides, carbonitrides or intermetallic compounds (e.g., in the grinding step) to provide a ground powder comprising Si, Ti, V, Ge, Ta, Pb, Y and / or Mn in the form of carbides, nitrides, carbonitrides or intermetallic compounds.

[0030] According to a fourth aspect of the present invention, there is provided a method for preparing a cemented carbide body as described herein, the method comprising: grinding powders of tungsten carbide, iron and chromium-containing material together; pressing the ground powder to form a green body; sintering the green body in a vacuum; and cooling the sintered body.

[0031] As an option, sintering is at a temperature of at least 1200°C.

[0032] As an option, sintering is at a temperature not exceeding 1300° C. and / or for a period of at least 15 minutes.

[0033] As an option, sintering is at a temperature of up to 1500°C.

[0034] Alternatively, sintering is at a temperature of about 1250°C to about 1480°C.

[0035] Optionally, sintering is continued for a period of at least 15 minutes.

[0036] As an option, the chromium-containing material is or comprises chromium carbide or chromium nitride.

[0037] Alternatively, the chromium carbide is Cr3C2.

[0038] As an option, the method further comprises adding Si, Ti, V, Ge, Ta, Pb, Y and / or Mn in the form of carbides, nitrides, carbonitrides or intermetallic compounds (e.g., in the grinding step) to provide a ground powder comprising Si, Ti, V, Ge, Ta, Pb, Y and / or Mn in the form of carbides, nitrides, carbonitrides or intermetallic compounds.

[0039] According to a fifth aspect of the present invention there is provided a block for forming a wall of a fusion nuclear reactor, the block comprising a cemented carbide body as described herein.

[0040] According to a sixth aspect of the present invention, there is provided use of a cemented carbide body as described herein in a fusion nuclear reactor. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Non-limiting examples for illustrating the present disclosure are described with reference to the accompanying drawings, in which:

[0042] Figure 1 is an optical microscope image of a cemented carbide body prepared according to Example 1 after etching in Murakami reagent;

[0043] Figure 2 is an optical microscope image of a cemented carbide body made according to Example 1 after etching in Nital reagent;

[0044] Figure 3 is an optical microscope image of a cemented carbide body prepared according to Example 2 after etching in Murakami reagent;

[0045] Figure 4 is an optical microscope image of a cemented carbide body made according to Example 2 after etching in Nital reagent;

[0046] Figure 5 is an optical microscope image of a cemented carbide body prepared according to Example 3 after etching in Murakami reagent;

[0047] Figure 6 is an optical microscope image of a cemented carbide body made according to Example 3 after etching in Nital reagent;

[0048] Figure 7is an optical microscope image of a cemented carbide body prepared according to Example 4 after etching in Murakami reagent;

[0049] Figure 8 is an optical microscope image of a cemented carbide body made according to Example 4 after etching in Nital reagent;

[0050] Fig. 9 is an optical microscope image of a cemented carbide body prepared according to Example 5 after etching in Murakami reagent;

[0051] Fig.10 is an optical microscope image of a cemented carbide body made according to Example 5 after etching in Nital reagent;

[0052] Fig.11 is a high resolution scanning electron microscope image of a cemented carbide body made according to Example 5 without etching; and

[0053] Fig.12 is a high-resolution scanning electron microscope image of the cemented carbide body prepared according to Comparative Example 1 without etching. DETAILED DESCRIPTION

[0054] A series of experiments were performed to identify the optimal range of chromium content. The composition of the laboratory batch of starting material is shown in Table 1.

[0055]

[0056]

[0057] Example 1

[0058] A laboratory batch of WC-Fe powder (10 kg) was prepared by grinding 500 g of Fe, 30 g of Cr3C2 powder and 9470 WC powder and 180 g of paraffin together with 30 kg of WC-Co balls in hexane. The WC powder had an average particle size of about 6 μm. The Fe powder had an average particle size of about 3 μm, and the Cr3C2 powder had an average particle size of about 2 μm. These components were ground together in a ball mill for 30 hours. The ETC (total carbon equivalent) value of this mixture was equal to nearly 5.93 wt.%.

[0059] After grinding, the resulting slurry was dried at a temperature of about 90°C and subsequently sieved, which produced a graded powder suitable for pressing in a mold. A cylindrical sample with a diameter of 20 mm and a height of 10 mm was pressed from the graded powder and sintered in a Sinter-HIP furnace at a temperature of 1280°C for 75 min (45 min vacuum + 30 min sintering at 40 bar Ar pressure).

[0060] As a result of the sintering process, fully dense samples were obtained without any inclusions of η phase or free carbon. The microstructure of one of these samples after etching in different reagents is shown in Figure 1 and Figure 2 In. Figure 1 As can be seen from the figure, the sample subjected to etching in the Murakami reagent does not contain the η phase, and as Figure 2 The microstructure contains some cementite, which is visible as white or light grey inclusions after etching in Nital reagent. No other carbide phases were found to be present in the microstructure except WC and cementite, which indicates that the amount of chromium carbide added during liquid phase sintering was completely dissolved in the binder phase. The sample was found to have a Vickers hardness value of nearly 15.5 GPa and a hardness of about 9 MPa m 1 / 2 The combination of hardness and fracture toughness is close to that of conventional WC-Co cemented carbide, see for example Roebuck B, Gee MG, Morrell R. Hardmetals-microstructural design, testing and property maps. In: Kneringer G, P, Wildner H, eds. Proceedings of the 15th International Plansee Seminar, Vol. 4. Reutte; 2001. pp. 245-66.

[0061] Afterwards, a trace amount (i.e., a small amount) of the graded powder was mixed with different amounts of tungsten metal powder having an average particle size of about 0.5 μm and carbon black in such a way that the ETC value was steadily reduced to 5.8 wt.% on the one hand and gradually increased to 6.1 wt.% at intervals equal to 0.02 wt.% C on the other hand. The samples from the graded powder mixture obtained in this way were pressed and sintered under the above conditions. Afterwards, a cross section was prepared and the presence of η phase and free carbon was checked. It has been determined that the carbon content range (under which η phase and free carbon are not present in the microstructure) is equal to about 0.14 wt.%, which is comparable to the carbon content range of conventional WC-Co cemented carbide.

[0062] Example 2

[0063] The samples were produced as in Example 1, except that 50 g of chromium carbide powder was added and the amount of WC was reduced accordingly to provide a 10 kg batch. As a result of the sintering process, a fully dense sample was obtained that did not contain any inclusions of eta phase or free carbon. Figure 3 As can be seen from the figure, the sample subjected to etching in the Murakami reagent does not contain the η phase, and as Figure 4 The microstructure contains some cementite, which is visible as white or light grey inclusions after etching in Nital reagent. No other carbide phases were found to be present in the microstructure except WC and cementite, which was confirmed by XRD studies. The sample was found to have a Vickers hardness value of nearly 15.7 GPa and a hardness of about 8.4 MPa m 1 / 2 The Babbitt fracture toughness value of Example 1 is lower than that of Example 1.

[0064] Example 3

[0065] The samples were produced as in Example 1, except that 80 g of chromium carbide powder was added and the amount of WC was reduced accordingly to provide a 10 kg batch. As a result of the sintering process, a fully dense sample was obtained that did not contain any inclusions of eta phase or free carbon. Figure 5 As can be seen from the figure, the sample subjected to etching in the Murakami reagent does not contain the η phase, and as Figure 6 The microstructure contains some cementite, which can be seen as white or light grey inclusions after etching in Nital reagent. This sample also contains mixed carbides (Cr,Fe) x C y inclusions, in Figure 6 The inclusions are visible as dark inclusions in the sample and this is confirmed by XRD studies. These mixed carbide inclusions have a dark brown color which is typical of mixed Cr-Fe carbides. The sample was found to have a Vickers hardness value of nearly 15.9 GPa and a hardness of about 7.6 MPa m 1 / 2 The Babbitt fracture toughness values ​​of Example 1 and Example 2 are lower than those of Example 1 and Example 2. This relatively low fracture toughness value is most likely related to the presence of mixed Cr-Fe carbide inclusions in the microstructure.

[0066] Example 4

[0067] The samples were produced as in Example 1, except that 150 g of chromium carbide powder was added and the amount of WC was reduced accordingly to provide a 10 kg batch. As a result of the sintering process, a fully dense sample was obtained that did not contain any inclusions of eta phase or free carbon. Figure 7 As can be seen from the figure, the sample subjected to etching in the Murakami reagent does not contain the η phase, and as Figure 8The microstructure contains many cementites, which are visible as white or light grey inclusions after etching in Nital reagent. The sample was found to have a Vickers hardness value of nearly 16.5 GPa and a hardness of about 7.4 MPa m 1 / 2 This is lower than the values ​​in Examples 1 and 2. This relatively low fracture toughness value is likely related to the fact that almost all of the Fe binder is converted into cementite.

[0068] Example 5

[0069] The samples were produced as in Example 1, except that 500 g of chromium carbide powder was added and the amount of WC was reduced accordingly to provide a 10 kg batch. As a result of the sintering process, a fully dense sample was obtained that did not contain any inclusions of eta phase or free carbon. Fig. 9 As can be seen from the figure, the sample subjected to etching in the Murakami reagent does not contain the η phase, and as Fig.10 The microstructure contains many cementites, which are visible as white or light grey inclusions after etching in Nital reagent. Fig.11 A HRSEM image of the microstructure is shown, indicating that the microstructure does not contain any pores. The sample was found to have a Vickers hardness value of nearly 16.5 GPa and a hardness of about 7.0 MPa m 1 / 2 The composition of Example 5 has a Babbitt fracture toughness value of 0.040777°, which is lower than that of Examples 1 and 2. Such low fracture toughness values ​​are likely related to the presence of mixed Cr-Fe carbide inclusions in the microstructure. Although the fracture toughness is lower than that of Examples 1 and 2, it is high enough to allow the composition of Example 5 to be used in the production of articles for neutron shielding.

[0070] Comparative Example 1

[0071] Samples were produced as in Example 1, except that 1000 g of chromium carbide powder was added and the amount of WC was reduced accordingly to provide a 10 kg batch. As a result of the sintering process, very porous samples were produced. The porosity was so high that the density could not be measured by hydrostatics. The fracture surface of one sample is shown in Fig.12 Such porous samples are not suitable for the production of articles for neutron shielding.

[0072] Comparative Example 2

[0073] The samples were produced as in Example 1, except that 5 g of chromium carbide powder was added and the amount of WC was reduced accordingly to provide a 10 kg batch. As a result of the sintering process, a fully dense sample containing inclusions of the η phase was obtained. 0.01 wt.% carbon black was added to the mixture and the sample was sintered in the same manner as in Example 1. As a result, inclusions of free carbon were present in the microstructure, indicating that the width of the two-phase region in this alloy was equal to or close to zero; in other words, when using this amount of chromium, it is impossible to produce a sample free of η phase and free carbon. Such materials are not suitable for the production of articles for neutron shielding.

[0074] While the invention has been particularly shown and described with reference to various embodiments, it will be understood by those skilled in the art that various changes in form and details may be made without departing from the scope of the invention as defined by the following claims.

Claims

1. A cemented carbide body for neutron shielding, the cemented carbide body containing WC, Fe and Cr, wherein the Cr is present in an amount of about 1 wt.% to about 150 wt.% relative to the Fe content, the cemented carbide body comprising WC grains, cementite grains, and Cr, W and C dissolved in an Fe-based binder matrix material.

2. The cemented carbide body according to claim 1, wherein The Cr is present in an amount of about 1 wt. % to about 90 wt. % relative to the Fe content.

3. The cemented carbide body according to claim 1 or claim 2, wherein: The Cr is present in an amount of about 1 wt. % to about 10 wt. % relative to the Fe content.

4. A cemented carbide body according to any preceding claim, wherein: The Cr is present in an amount of about 1 wt. % to about 6 wt. % relative to the Fe content.

5. A cemented carbide body according to any preceding claim, having a Vickers hardness of at least 15 GPa.

6. A cemented carbide body according to any preceding claim having a strength of at least 7 MPa m 1 / 2 Babbitt fracture toughness.

7. A cemented carbide body according to any preceding claim which is substantially free of free carbon.

8. A cemented carbide body according to any preceding claim which is substantially free of eta phase.

9. A cemented carbide body according to any preceding claim, wherein: The porosity of the cemented carbide body is less than 0.1%.

10. A cemented carbide body according to any preceding claim, further comprising up to 5 wt. % Si, Ti, V, Ge, Ta, Pb and / or Y and combinations thereof, relative to the iron content.

11. A cemented carbide body according to any preceding claim, further comprising up to 50 wt. % Mn relative to the Fe content.

12. A method of preparing a cemented carbide body according to any preceding claim, the method comprising: grinding powders of tungsten carbide, iron and chromium-containing material together; pressing the ground powder to form a green body; sintering the green body in vacuum; as well as The sintered body is cooled.

13. The method according to claim 12, wherein: The sintering is at a temperature of at least 1200°C.

14. The method according to claim 12 or claim 13, wherein: The sintering is at a temperature of up to 1500°C.

15. The method according to any one of claims 12 to 14, wherein: The sintering is at a temperature of about 1250°C to about 1480°C.

16. The method according to any one of claims 12 to 15, wherein: The sintering lasts for a period of at least 15 minutes.

17. The method according to any one of claims 12 to 16, wherein: The chromium-containing material is chromium carbide or chromium nitride.

18. The method according to claim 17, wherein: The chromium carbide is Cr3C2.

19. A method according to any one of claims 12 to 18, when dependent on claim 10 or 11, further comprising adding Si, Ti, V, Ge, Ta, Pb, Y and / or Mn in the form of carbides, nitrides, carbonitrides or intermetallic compounds.

20. A block for forming the wall of a fusion nuclear reactor, the block comprising a cemented carbide body according to any one of claims 1 to 11.

21. Use of a cemented carbide body according to any one of claims 1 to 11 in a fusion nuclear reactor.